Gravidez na adolescência: um estudo na comunidade do rio Itacuruçá médio - COSTA, Ana Léa do Socorro Coutinho da (2024)
Adolescence isa period ofgreat changesthat further increasethe occurrenceof anunplannedorunwanted pregnancy, whether or not a solution to the pregnant teenager, because motherhood can bring maturity, and may contribute to aggravate your social and economic problems. Besides ripening, with the birth of the child, increase the responsibilities that are charged by the family and society. The result of a teenage pregnancy has several effects on the adolescent life, can vary from school dropouts to entry for a riotous living, making use of illegal substances when characterized by an unplanned pregnancy. The choice of this topic was first imposed by its relevance and timeliness and second, that we analyze more closely the reality of teenage pregnancy in the vicinity of Rio Itacuruçá region Islands Municipality Abaetetuba. The methodology adopted for the preparation of this work was based in a review of the literature on this topic, supplemented by interviews with a sample of 10 adolescent mothers who were invited to participate and five teachers. Thus, it was possible to analyze the problem of teenage pregnancy and seek to realize the contribution of teachers, the community, especially families, for the prevention of early pregnancy. We hope this work can contribute to the professional education, health, and social assistance to realize the world of teenagers mainly in pregnant condition, and especially to "stimulate" the teachers to improve their skills in communicating with adolescents about the sex education.